2017
DOI: 10.1097/prs.0000000000003076
|View full text |Cite
|
Sign up to set email alerts
|

Tendon Rupture and Tenosynovitis following Internal Fixation of Distal Radius Fractures: A Systematic Review

Abstract: This systematic review provides an update on the literature regarding tendon-related complications in the management of distal radius fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 73 publications
0
29
0
1
Order By: Relevance
“…In a systematic review of tendon complications following open reduction and internal fixation of distal radius fractures, Azzi et al similarly found a low incidence of tendon complications following volar plating. 69 Their systematic review reported a 7.5 versus 4.5% tenosynovitis and 1.7 versus 1.4% tendon rupture rate following dorsal plating and volar locked plating, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…In a systematic review of tendon complications following open reduction and internal fixation of distal radius fractures, Azzi et al similarly found a low incidence of tendon complications following volar plating. 69 Their systematic review reported a 7.5 versus 4.5% tenosynovitis and 1.7 versus 1.4% tendon rupture rate following dorsal plating and volar locked plating, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Beyond the distress of both surgeon and patient, this attention is also justified from a cost standpoint. Distal radius hardware removal for plate prominence and tendon rupture cost the health care system over $15.2 million annually, 10,[21][22][23] and this surgical expense is dwarfed by the cost of time of work, extra clinic visits, therapy, prescription drug, and caretaker costs, which easily double or even triple this number. 2 This expense is an additional motivating force toward design innovation, which has succeeded in bringing a plethora of new plates to market.…”
Section: Discussionmentioning
confidence: 99%
“…6 Flexor tendon rupture is the most well described late complication, with rates reported between 0.8 to 12%, [7][8][9] and a recent meta-analysis finding the incidence to be 1.5%. 10 The two most common flexor tendons affected are the flexor pollicis longus (FPL) and the index flexor digitorum profundus (FDP), which are associated with 57 to 75 and 15% of cases, respectively. 11,12 A well-recognized factor leading to tendon irritation is plate placement in relation to the most distal volar ridge of the radial metaphysis, known as the watershed line.…”
mentioning
confidence: 99%
“…Auch einliegendes Osteosynthesematerial, wie z. B. bei palmar versorgter distaler Radiusfraktur, kann durch mechanische Irritation der darüber liegenden Beugesehnen zu einer gedeckten Verletzung führen [1,4]. [22].…”
Section: Verletzungsursachenunclassified